Análisis de los TLC suscritos con los países asiáticos - Facilitación del Comercio y Procedimientos Aduaneros - Guadalupe Báscones, Julio (2017)
The opening of Peru to foreign markets in the past 20 years is a consequence of the signature of several Free Trade Agreements (FTA) with our main partners in business, both on a bilateral and multilateral level. In this article, on the one hand, important changes to customs regulations concerning obligations arose from the signature of several FTA will be analyzed and, on the other hand, a comparative analysis regarding regulations about facilitation of commerce and customs procedures contained in FTA signed with our main Asian partners in business will be developed.